Implementasi Sensor Ultrasonik HC-SR04 dengan Arduino dan LabVIEW untuk Pengukuran Level Air - Arifuddin, Fikri; Rafsyam, Yenniwarti (Spektral, 2025)
This study discusses the implementation of the HC-SR04 ultrasonic sensor using Arduino for distance measurement, and the integration of measurement results into LabVIEW. HC-SR04 is used to measure the distance of objects with the principle of ultrasonic wave reflection. Data generated by Arduino is sent to LabVIEW via serial communication, then visualized and analyzed. This method allows real-time data processing and provides interactive visualization to facilitate understanding of measurement results. This experiment successfully demonstrated that the combination of Arduino, HC-SR04, and LabVIEW can provide accurate measurement results with fast response in an air level monitoring system.